Association between dietary inflammatory index and all-cause mortality in US adults with dermatitis: a population-based cohort study - Liu, Yan; Liao, Jie; Zhang, Jieyi; Zhou, Rang; Li, Weiqi; Tao, Yuanrong; Qin, Yuesi (Frontiers in Nutrition, 2024)
Background: While dermatitis management is primarily symptomatic, the role of diet in symptom exacerbation and improvement is increasingly recognized. The Dietary Inflammatory Index (DII), a quantitative assessment tool for dietary inflammatory potential, has been associated with various chronic diseases but remains understudied in dermatitis. This cohort study investigated the association between DII scores and all-cause mortality among patients with dermatitis. Methods: The study included 1074 patients with dermatitis and complete dietary intake records from the National Health and Nutrition Examination Survey (NHANES) 1999-2004. The DII scores were calculated using two 24-hour dietary recalls and dietary supplement intakes and the consumption of 28 foods with known pro- or anti-inflammatory properties. All-cause mortality information was from the National Death Index, censored on December 31, 2019. Multivariable Cox hazards regression models, restricted cubic spline (RCS) models, and subgroup analyses were employed to evaluate the association of DII with all-cause mortality, adjusting for potential confounders. Results: The 1074 patients were divided into DII tertiles (T1: n=358, median age 40 years, DII -3.91, 0.06; T2: n=296, median age 40 years, DII 0.06, 1.88; T3: n=237, median age 39 years, DII 1.88, 4.39). The study revealed a positive correlation between higher DII scores and increased all-cause mortality risk among patients with dermatitis (fully-adjusted model, HR = 1.13, 95% CI 1.02, 1.27, p = 0.026). This association was more pronounced in adults over 45 years, with the highest DII tertile indicating a 2.42-fold increased mortality risk (95% CI 1.15, 5.07, p = 0.019) compared with the lowest tertile. The RCS model confirmed a linear dose-response trend (p for non-linear = 0.183), validating the relationship. Conclusion: Elevated DII scores are associated with an increased risk of all-cause mortality in patients with dermatitis, suggesting that the dietary inflammatory potential may impact health outcomes in this population. The findings underscore the importance of dietary interventions in dermatitis management, especially for middle-aged and older adults. Future research with larger cohorts and a longer follow-up is warranted to validate the findings.